Color Change, Biaxial Flexural Strength, and Fractographic Analysis of Resin-Modified CAD/CAM Ceramics Subjected to Different Surface Finishing Protocols - Mona Alhassan; Ahmed Maawadh; Nawaf Labban; Nourah Shono; Ahmad Alebdi; Saleh Alhijji; Abdulelah M. BinMahfooz (Applied Sciences, 2023)
This in vitro study compared the color change (∆E) and biaxial flexural strength (BFS) of two resin nanoceramics (LU and CS) and two polymer-infiltrated ceramic networks (VE and CU) after different surface finishing protocols. A total of 192 discs (12 × 1.2 mm2) were prepared from the materials (n = 48) and then polished with 1200-grit silicon carbide paper, followed by roughening with a 30 µm grit diamond bur. According to the surface finishing applied, the discs from each material category were categorized into four groups: control group (no finishing), polishing (MP), glazing (OG), or a combination of MP and additional polishing (MP+PP). Following surface finishing, all the discs were immersed in a coffee beverage to simulate one year of clinical use. A spectrophotometer and universal testing machine were used to measure the ∆E and BFS, respectively. Fractographic analysis was performed using scanning electron microscopy images. Multivariate analysis of variance was used for the statistical analysis, followed by one-way ANOVA and post hoc Dunnett’s test (a = 0.05). The ∆E and BFS were significantly impacted by material type and surface finishing (p ≤ 0.05). Irrespective of the materials and finishing, untreated LU and OG-treated VE specimens demonstrated the highest (2.98 ± 0.36) and lowest (1.21 ± 0.33) color changes. Regarding BFS, untreated CU and OG-treated CS specimens demonstrated the lowest (121.88 ± 2.08 MPa) and highest (174.17 ± 3.83 MPa) values. Surface finishing using glazing resulted in the highest BFS and lowest ∆E compared to other surface finishing protocols for the tested materials. VE demonstrated the least color changes, and CS showed the highest BFS following surface finishing of the materials tested. Surface finishing is material dependent; thus, it is critical to use the best surface finishing protocol in a clinical setting.